Status nutrisi dan asosiasinya dengan menarche pada siswa SMP di Manokwari Papua Barat Indonesia - Preisilia Fristy; Febriza Dwiranti; Elda Irma Jeanne Joice Kawulur (Postgraduate, University of Mataram, 2024)
Menarche is the occurrence of the first menstruation in girls naturally. The nutritional status of girls influences age at menarche. Nutritional status has a role in the formation of hormones that affect the occurrence of menarche and a person's nutritional status can reflect the condition of his body. This study aims to investigate the relationship between nutritional status and menarche age in junior high school students in Manokwari, West Papua. The design of this study uses a descriptive method with data collection techniques with purposive sampling and a cross-sectional approach. Nutritional status measurement is carried out through the measurement of Body Mass Index (BMI) The age of menarche is taken based on the age of the first menstruation. The relationship between nutritional status and age at menarche was analyzed through a chi-square test. This study prove that the nutritional status of junior high school students in Manokwari was mostly normal category (80.9%). The overnutrition category was quite high (19% overweight and 10% obese). The average age at menarche was 12.51 years, of which 91% of junior high school students have experienced menarche. Statistical analysis proved that there was no significant relationship between nutritional status and age at menarche with a p-value 0.132.